2008
DOI: 10.1021/jp800680w
|View full text |Cite
|
Sign up to set email alerts
|

p53-Induced DNA Bending: The Interplay between p53−DNA and p53−p53 Interactions

Abstract: Specific p53 binding-induced DNA bending and its underlying driving forces are crucial for the understanding of selective transcription activation. Diverse p53-response elements exist in the genome. However, it is not known what determines the DNA bending and to what extent. In order to gain knowledge of the forces that govern the DNA bending, molecular dynamics simulations were performed on a series of p53 core domain tetramer-DNA complexes in which each p53 core domain was bound to a DNA quarter site specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…The dimer-dimer interface observed here has a larger contact area and better chemical and shape complementarity than that seen in the chemically trapped complex. Moreover, the N-terminal tail, which is predicted by modeling analyses to mediate dimer-dimer interactions (Cho et al, 1994; Ho et al, 2006; McLure and Lee, 1998; Pan and Nussinov, 2008), is disordered in the chemically trapped complex. In the present structure, this region is indeed located at the dimer-dimer interface and engages in extensive protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The dimer-dimer interface observed here has a larger contact area and better chemical and shape complementarity than that seen in the chemically trapped complex. Moreover, the N-terminal tail, which is predicted by modeling analyses to mediate dimer-dimer interactions (Cho et al, 1994; Ho et al, 2006; McLure and Lee, 1998; Pan and Nussinov, 2008), is disordered in the chemically trapped complex. In the present structure, this region is indeed located at the dimer-dimer interface and engages in extensive protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results on the interactions of the charged tail with the DNA and its role in modulating the orientation of the Tet domain relative to the DNA support the hypothesis that the tails can further promote conformational change in the p53-DNA complex. Thus, the tails are important not only in order to search for the location of cognate sites but also to support specific interactions with the DNA (e.g., DNA bending, as observed in the crystal structure of the specific complex of p53 with some of its response elements [75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…This differential affinity of p53 for its REs allows the nuclear concentration of the protein to be one determining factor in how target genes are activated, and hence also for which cellular outcome occurs after genotoxic stress (Szak et al 2001;Lokshin et al 2005). The proclivity of a p53 RE to bend may also play a large role in determining the affinity and stability of p53 with its cognate element (Batta and Kundu 2007;Pan and Nussinov 2008). Intriguingly, a genome-wide study has shown that not all sites bound by p53 are in fact transcriptionally activated (Wei et al 2006a), raising the possibility that other coactivators and/or a specific modification status of p53 are needed to induce robust activation of select p53 target genes (discussed later).…”
Section: P53 Response Elementsmentioning
confidence: 99%